Back Cover: Unravelling the Correlation between the Aspect Ratio of Nanotubular Structures and Their Electrochemical Performance To Achieve High‐Rate and Long‐Life Lithium‐Ion Batteries (Angew. Chem. Int. Ed. 49/2014). Issue 49 (22nd October 2014) - Tang, Yuxin; Zhang, Yanyan; Deng, Jiyang; Qi, Dianpeng; Leow, Wan Ru; Wei, Jiaqi; Yin, Shengyan; Dong, Zhili; Yazami, Rachid; Chen, Zhong; Chen, Xiaodong
<x xml:space="preserve">Abstract</x> Understanding the relationship between the nanostructure of an electrode and its electrochemical performance is crucial for the development of high‐perfomance lithium‐ion batteries. In their Communication on page 13488 ff., Z. Chen, X. Chen, and co‐workers report that the aspect ratio of nanotubular materials determines battery performance at high charging/discharging rates. Their proof‐of‐concept batteries are very promising for energy‐storage systems in electrical vehicles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>